Combating Sexual Violence and Strengthening Child Protection: An Analysis of Policy Implementation in Indonesia - Hendry; Dey Ravena; Syafrinaldi Syafrinaldi (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Legal protection for victims of sexual violence constitutes a fundamental aspect of the rule of law and the realization of human rights. Beyond imposing sanctions on perpetrators, the state bears responsibility for ensuring justice, recovery, and the restoration of victims’ dignity, particularly for children who are highly vulnerable to physical and psychological harm. This study aims to analyze the implementation of policies addressing sexual violence in Indonesia, with a focus on their effectiveness in providing legal protection for child victims, and to develop a conceptual model for strengthening such protection. This research employs a normative juridical method, drawing on statutory regulations, judicial decisions, legal doctrines, and relevant theoretical frameworks. Using a descriptive-analytical approach, the study systematically examines the coherence between legal norms and their practical enforcement. The findings indicate that, despite significant normative progress in Indonesia’s legal framework on sexual violence, the implementation of these policies remains suboptimal. Persistent structural and functional gaps between legal formulation and law enforcement practices hinder the realization of effective protection for child victims. From the perspective of criminal law policy, this underscores the discrepancy between “law in the books” and “law in action.” To address these challenges, the study proposes an integrated policy implementation model consisting of three interrelated components: (1) a national regulatory framework as the normative foundation for guaranteeing children’s rights; (2) internal organizational policies focused on child safeguarding mechanisms; and (3) a community-based protection approach that positions local communities as key actors in prevention and response. This model offers a comprehensive strategy for enhancing the effectiveness of legal protection for child victims of sexual violence in Indonesia and provides broader insights for similar jurisdiction.